Prevention of Polyglycolic Acid-Induced Peritoneal Adhesions Using Alginate in a Rat Model. (21st May 2015) - Matoba, Mari; Hashimoto, Ayumi; Tanzawa, Ayumi; Orikasa, Taichi; Ikeda, Junki; Iwame, Yoshizumi; Ozamoto, Yuki; Abe, Rie; Miyamoto, Hiroe; Yoshida, Chiko; Hashimoto, Toru; Torii, Hiroko; et al.
Abstract : Postoperative intra-abdominal or intrathoracic adhesions sometimes cause significant morbidity. We have designed three types of alginate-based treatments using strongly cross-linked (SL), weakly cross-linked (WL), and non-cross-linked (NL) alginate with calcium gluconate. In rat experiments, we compared the antiadhesive effects of the three types of alginate-based treatments, fibrin glue treatment (a standard treatment), and no treatment against adhesions caused by polyglycolic acid (PGA) mesh (PGA-induced adhesions). The antiadhesive materials were set on the PGA sheet fixed on the parietal peritoneum of the abdomen. Fifty-six days later, the adhesions were evaluated macroscopically by the adhesion scores and microscopically by hematoxylin-eosin staining and immunostaining. We also tested the fibroblast growth on the surface of the antiadhesive materials in vitro . The antiadhesive effects of WL and NL were superior to the no treatment and fibrin glue treatment. A microscopic evaluation confirmed that the PGA sheet was covered by a peritoneal layer constructed of well-differentiated mesothelial cells, and the inflammation was most improved in the NL and WL. The fibroblast growth was inhibited most on the surfaces of the NL and WL. These results suggest that either the WL or NL treatments are suitable for preventing PGA-induced adhesions compared to SL or the conventional treatment.